TANTANGAN TERHADAP PANCASILA SEBAGAI IDEOLOGI DAN DASAR NEGARA PASCA REFORMASI - Husein Muslimin (Jurnal Cakrawala Hukum, 2016)
Pancasila is a basic value from Indonesia as a nation, it is also a basic ground in nation and country life sinceIndonesia independence. Regarding how important the existence of Pancasila, it is must be going through along and hard process to create Pancasila. This paper will highlight and study Pancasila creation as anideology and country basic ground. This paper will also study about Pancasila position after reformation timeand how those ideology implemented in challenging changes in after reformation.